Tanggung Jawab Pemerintah terhadap Pekerja yang Mengalami Kecelakaan Kerja Akibat Kelalaian Perusahaan dalam Prinsip Kesehatan dan Keselamatan Kerja (K3) - Johannes Evan Budiman; Ariawan Gunadi (CV Rewang Rencang, 2024)
This research discusses the government's responsibility towards workers who experience work accidents due to company negligence in the application of Occupational Health and Safety (OHS) principles. Using normative research methods, this study analyzes regulations and policies related to occupational health and safety in Indonesia, including the role of the government as a regulator and supervisor in the implementation of the occupational health and safety system. The results show that although there are various regulations governing occupational health and safety, implementation in the field still faces many obstacles, including weak supervision and sanctions against violating companies. The government is responsible for creating policies that protect workers, overseeing their implementation, providing education, and providing compensation through mechanisms such as the Work Accident Insurance. This study highlights the importance of revising and strengthening occupational health and safety regulations to be more relevant to modern challenges and provide maximum protection for workers.